The thermo-hygrometric properties of multi-purpose historic buildings - Byrne, Niall (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2014)
The concept of sustainability is a multi-faceted one, with environmental, social and economic aspects all requiring consideration when assessing the sustainability at a micro or macro scale. Accordingly, when considering measures aimed to improve the sustainability of a building, town or city, improving the environmental performance of the area, although important, may not suffice in terms of making an area more sustainable. For example, ongoing preservation of collection items in museums, libraries and archives will contribute to a city both socially and economically as it will be inherent in the culture of the area and will generate revenue from the resulting tourism.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin